Study of Sexual dimorphism of human patella by measuring maximum height, width, thickness - Akter , Sheuli; Siddiqua, Dilruba; Khatoon, Mahmuda; Shahin, Rebeka; Rahman, Mustafezur; Mowtoshee, Nusrat Rumman (Bangladesh Journal of Medical Science, 2025)
Background Largest sesamoid bone in our body is patella which develops within the tendon of the quadriceps femoris muscle. Therefore, its morphology is dependent on the strain generated by the quadriceps muscle and can be modified by several cultural-ethnic factors. Males have comparatively larger muscle build compared to females, so this small bone would show a remarkable degree of sexual dimorphism. Methods Cross sectional, analytical type of study carried out in the Department of Anatomy, Dhaka Medical College, Dhaka, from January 2018 to June 2019. One hundred and fifty (150) dry adult human left patella of unknown sex were collected. The study samples were grouped into male and female by discriminant function analysis and 92 male and 58 female bones were found. Maximum patellar height, width, thickness were measured by digital slide calipers. Results The mean ± SD of maximum patellar height, width, thickness, were significantly higher in male than female. Conclusion The morphometric measurements of the left patella showed that Significant difference exists between male and female patellae. The maximum height, width and thickness of patellae were significantly higher in male than female. BJMS, Vol. 24 No. 03 July’25 Page : 853-857